The impact of private equity on firms׳ patenting activity - Amess, Kevin; Stiebale, Joel; Wright, Mike (Elsevier, 2015)
The paper analyses the impact of private equity (PE) backed leveraged buyouts (LBOs) on innovative output (patenting). Using a sample of 407 UK deals we find that LBOs have a positive causal effect on patent stock and quality-adjusted patent stock. Our results imply a 6% increase in quality-adjusted patent stock three years after the deal. The increase in innovative activity is concentrated among private-to-private transactions with a 14% increase in the quality-adjusted patent stock. We also find evidence suggesting that PE firms facilitate the relaxation of financial constraints. In sum, our findings suggest that PE firms do not promote short-term cost-cutting at the expense of entrepreneurial investment opportunities with a long-term pay-off.